Terrestrial mammal species richness and composition in three small forest patches within an oil palm landcape in Sabah, Malaysian Borneo - Henry Bernard; Esther L Baking; Anthony J Giordano; Oliver R. Wearn; Abdul Hamid Ahmad (Mammalogical Society of Japan, 2014)
Small and highly degraded forest patches are usually scattered across oil palm plantation landscapes and often exist as permanent features. By using a combination of camera-trapping and line-transect methods, we evaluated the usefulness of three such forest patches (< 30 ha) for terrestrial mammal species conservation in a mature oil palm plantation located near (< 1.7 km) a large continuous tract of logged forest in eastern Sabah, Malaysian Borneo. Of the 29 terrestrial mammal species recorded in this study, 28 were found in the continuous logged forest habitat including six species that are either large-bodied, wide ranging, locally rare or are of high conservation concern. In comparison, 18 species were recorded across the three forest patches collectively; consisting mostly of species that are widespread, well-adapted to living in highly modified habitats and of low conservation concern. The presence of small forest patches within the oil palm habitat matrix seemed to be useful to some extent for some mammal species. However, many of the species were likely only transient in this habitat. The maintenance of large continuous tracts of natural forest is critical to the continued survival of many terrestrial mammal species on Borneo, particularly for species that are of high conservation value.